2023
DOI: 10.3389/fnmol.2023.1172366
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR inhibitor rapamycin suppresses trigeminal neuropathic pain and p-MKK4/p-p38 mitogen-activated protein kinase-mediated microglial activation in the trigeminal nucleus caudalis of mice with infraorbital nerve injury

Abstract: Neuropathic pain caused by trigeminal nerve injury is a typical refractory orofacial chronic pain accompanied by the development of hyperalgesia and allodynia. We previously demonstrated that the mammalian target of rapamycin (mTOR) inhibitor rapamycin suppressed orofacial formalin injection-induced nociception; however, the underlying mechanism is unclear, and it is unknown whether it can reduce trigeminal neuropathic pain. In mice, left infraorbital nerve and partial nerve ligation (ION-pNL) was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
0
1
Order By: Relevance
“…46) Moreover, Yeo and Roh have recently reported that mechanical and cold allodynia two weeks after left infraorbital nerve injury and partial nerve ligation were significantly reduced just 1 h after rapamycin administration, which is closely associated with the modulation of microglial activation in in the trigeminal nucleus caudalis. 47) However, we showed here that neither bortezomib nor rapamycin affected Iba1-positive cells in the dorsal horn of the spinal cord. It has also been reported that astrocytes, but not microglia, are activated in the spinal dorsal horn during the chronic phase of a mouse model of bortezomib-induced peripheral neuropathy, 25) which is consistent with our observations and suggests that microglia are not strongly associated with analgesic effects in this mouse model.…”
Section: Discussioncontrasting
confidence: 57%
“…46) Moreover, Yeo and Roh have recently reported that mechanical and cold allodynia two weeks after left infraorbital nerve injury and partial nerve ligation were significantly reduced just 1 h after rapamycin administration, which is closely associated with the modulation of microglial activation in in the trigeminal nucleus caudalis. 47) However, we showed here that neither bortezomib nor rapamycin affected Iba1-positive cells in the dorsal horn of the spinal cord. It has also been reported that astrocytes, but not microglia, are activated in the spinal dorsal horn during the chronic phase of a mouse model of bortezomib-induced peripheral neuropathy, 25) which is consistent with our observations and suggests that microglia are not strongly associated with analgesic effects in this mouse model.…”
Section: Discussioncontrasting
confidence: 57%